Empowering women in Indonesia’s fishing communities: Overcoming structural barriers for economic resilience - Dalimunthe, Ritha F; Nauly, Meutia; Fachry, Mardiana Ethrawaty; Dwiningrum, Siti Irene Astuti; Siregar, Muhammad Bangun; Ramadani; Putra, Rizki (Research Journal in Advanced Humanities, 2025)
This study examines the challenges and opportunities faced by women in Indonesia’s fishing communities, focusing on their critical contributions to household and community resilience. The research highlights systemic barriers such as gender disparities in resource ownership, limited access to financial services, and low digital literacy levels. Utilizing the Harvard Analytical Framework, the study analyzes data collected from 120 participants through surveys, in-depth interviews, and field observations across Medan, Yogyakarta, and Makassar. Key findings reveal significant inequities in resource distribution and leadership roles alongside opportunities for digital empowerment. Policy recommendations emphasize enhancing access to capital, fostering digital literacy, and promoting inclusive leadership. The study concludes that addressing these barriers is essential for achieving gender equality and sustainable economic development in fishing communities. Practical implications include the design of targeted interventions to empower women as drivers of financial resilience